Successful Management of Cystic Endometrial Hyperplasia Pyometra Complex in a Labrador She dog - Singh, Nikita; Chauhan, Shailendra Singh; Singh, Jaswant; Chauhan, Shailendra Singh; Kumar, Rajesh (The Indian Journal of Animal Reproduction, 2025)
The six-year-old female Labrador presented with complaints of vomiting, restlessness, decreased appetite, and a scanty amount of vaginal discharge. Based on the history and clinical examinations of the patient the diag nosis of this case was done as cystic endometrial hyperplasia-pyometra complex. Surgical intervention (ovari ohysterectomy) was performed, followed by post-operative management. The patient showed an uneventful recovery.
Keywords: Cystic endometrial hyperplasia; CEH; Ovariohysterectomy; Pyometra